Hyperthermia don't affect hydric status of acclimatized cyclists on the self-pace submaximal exercise - Silva, R.; Ryker, B.; Sampaio, N. F.; Brito, C. J.; Viana, B.; Pires, F. O. (Journal of Science and Cycling, 2017)
Introduction Training acclimatization has been reported as a positive component focused on decrement of negative effects, caused by hyperthermia, on endurance exercise performance (Lorenzo et al., 1985, Journal Applied Physiology 109, 1140-1147/ Cheung, 2007, Applied Physiology, Nutrition, and Metabolism, 32, 808-817). However, few investigations have been made about hydric effects on this performance on submaximal exercise controlled by ratings of perceived exertion (RPE).